Strategy and war planning in the British navy, 1887-1918 - Grimes, Shawn T. (Boydell Press, 2012)
The book demonstrates how France and Russia were originally seen as the potential enemies, with the focus changing to Germany in the early years of the twentieth century. Throughout the period, the book argues, Britain had a consistent, well-developed strategy.